Pharmaceutical Stability Testing to Support Global Markets - Huynh-Ba, Kim.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
The International Conference of Harmonization (ICH) has worked on har- nizing the stability regulations in the US, Europe, and Japan since the early 1990s. Even though the Stability Guidelines Q1A (R2) was issued over a decade ago, issues surrounding this arena continue to surface as the principles described in the guideline are applied to different technical concentrations. As a result, the stability community has continued to discuss concerns and find ways of harmonizing regulatory requirements, streamlining practices, improving processes in order to bring safe and effective medical supplies to the patients around the world. In 2007, the American Association of Pharmaceutical Scientists (AAPS) Stability Focus Group organized two workshops – the Stability Workshop and the Degradation Mechanism Workshop. These meetings attracted many industry scientists as well as representatives from several regulatory agencies in the world to discuss important topics related to pharmaceutical stability practices. Recognizing the importance of documenting these discussions and with the permission of AAPS, I have worked with speakers to assemble a collection of 30 articles from presentations given at these two meetings, mainly the Stability Workshop. I trust that this book will be beneficial to all of you in providing guidance and up-to-date information for building quality stability programs. v Freedom of our mind is Mother of all inventions.
Section I -- Stability Studies in a Global Environment -- Regulatory Perspectives on Product Stability -- Current International Harmonization Efforts -- Update on the WHO Stability Guideline -- Development of a Regional Guideline for the Eastern Mediterranean Region -- The Challenge of Diverse Climates: Adequate Stability Testing Conditions for India -- Requirements for South East Asian Markets -- The Role of USP Monographs in Stability Testing -- Regulatory Requirements for Stability Testing of Generics -- Stability Design for Consumer Healthcare Products -- Challenges of Drug/Devices Pharmaceutical Products -- Practical Challenges of Stability Testing of Nutraceutical Formulations -- Setting Tolerances for Instrument Qualification USP Chapter -- Technical Concepts for Stability Program -- The Concept of Quality-by-Design -- Forced Degradation and Its Relation to Real Time Drug Product Stability -- Low Level Impurities in Drug Substances and Drug Products and the Analytical Challenges in Identification and Quantitation -- Stability of Repackaged Products -- Packaging-Induced Interactions and Degradation -- An Overview of Physical Stability of Pharmaceuticals -- Stability of Split Tablets -- Temperature Monitoring During Shipment and Storage -- Introducing a Science-Based Quality by Design Concept to Analytical Methods Development -- Stability Data and Operational Practices -- Optimizing Stability Data Package to Facilitate NDA/MAA Approval -- Maximize Data for Post Approval Changes -- Use of Statistics to Establish a Stability Trend: Matrixing -- Setting Specifications for Drug Substances -- Setting Specifications for Drug Products -- Highlights of Investigating Out-of-Specifications Test Results -- Strategies for Ensuring Regulatory and cGMP Compliance of Outsourced Stability Programs -- Building and Developing of Relationships with Third Party Laboratories -- Outsourcing Stability Testing: A Tool for Resource and Risk Management.
Keywords: Pharmacology; Pharmacology/Toxicology.